Tanzania manufacturing sector in response to trade liberalization: A case of pharmaceutical manufacturing - Gesoreka, George (Mzumbe University, 2024)
A dissertation submitted to Dar es Salaam Campus College in the partial fulfilment for the award of Master Degree of Business Administration (MBA) in Mzumbe University